DILEMA KEHIDUPAN ANAK DALAM SENI LUKIS REALIS KONTEMPORER - MEICHEL ORLANDO. S Drs. Abd. Hafiz, M.Pd., Drs. Mediagus, M.Pd. (Serupa The Journal of Art Education, 2018)
The purpose final work of raising the child’s life dilemma is affirm to the commnity to always prosper the lives of children, especially prosperous, for their love and aducation. The authors realize that children who are currently attending school will become leaders and pioneers of the national awakening of this beloved country. The method of creating this work is carried out in strages, namely: The preparation, the elaboration, the syinthesis phase, the realization of the concept, to the finishing of the work process. Ten work are with various kind of displays with children’s objects and a girl. Ten final work that writed with media acrylic on canvas are: "Key Children", "Jealousy", Hidden Anger, Regret, "They Are Just Like Us", Embracing Friends, "Portrait of Motivators", Carrying Grief, Letting, and Changing Attitudes.Kata kunci: Dilema, Kehidupan Anak, Seni Lukis Realis Kontemporer